2004
DOI: 10.1111/j.0022-202x.2004.22301.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Aberrations and Survival in Cutaneous T Cell Lymphomas

Abstract: Information on chromosomal aberrations in cutaneous T cell lymphomas (CTCL), is scarce. In this study, comparative genomic hybridization (CGH) was used to analyze chromosomal imbalances (CI) in 32 patients with CTCL. CI were detected in 21 patients (66%). Euchromatic loss (dim) was localized most frequently (>16%) at the chromosomal regions 17p (28%), 13q (25%), 10q (16%), and 6q (19%), and gain of chromatin (enh) at 7 (25%), 8q (25%), and 17q (16%). The pattern dim6q-enh7-enh8-dim13 was the most frequent comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
59
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 35 publications
13
59
2
Order By: Relevance
“…Conventional comparative genomic hybridization studies, together with a literature compilation of 166 mycosis fungoides and SS cases, have not detected 9p21 deletion as a recurrent feature of either mycosis fungoides or SS. 27,29 Several array-based comparative genomic hybridization studies also failed to detect CDKN2A-CDKN2B deletion in patients with either mycosis fungoides or SS. 42,43 For patients with transformed mycosis fungoides, our results agree extensively with those obtained by van Doorn et al 30 using a BAC arraybased comparative genomic hybridization approach with 1-Mb resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional comparative genomic hybridization studies, together with a literature compilation of 166 mycosis fungoides and SS cases, have not detected 9p21 deletion as a recurrent feature of either mycosis fungoides or SS. 27,29 Several array-based comparative genomic hybridization studies also failed to detect CDKN2A-CDKN2B deletion in patients with either mycosis fungoides or SS. 42,43 For patients with transformed mycosis fungoides, our results agree extensively with those obtained by van Doorn et al 30 using a BAC arraybased comparative genomic hybridization approach with 1-Mb resolution.…”
Section: Discussionmentioning
confidence: 99%
“…27 Nor did comparative genomic hybridization studies of both mycosis fungoides and SS cases find 9p21 loss as a recurrent imbalance of these lymphomas. 28,29 However, recent array-comparative genomic hybridization data obtained by the Leiden University group identified 9p21 loss in 41% of patients, with mycosis fungoides associated with lower survival rate. 30,31 By comparison, the deletion was not found in patients with SS.…”
Section: And Gil and Peters 5 )mentioning
confidence: 99%
“…The abnormalities of ALKÀALCL do not fully overlap with whose reported for other T-cell neoplasms, but can be shared with primary cutaneous ALCL. (11,45,57,58) The last observation is intriguing, indicating a high similarity between these two types, despite their diverse clinical features and outcomes, with a much better prognosis observed for primary cutaneous ALCL. (59) Two translocations have been recently reported in ALKÀALCL.…”
Section: Nodal Lymphomasmentioning
confidence: 99%
“…As compared with most hematological malignancies, the information on genetic aberrations in CTCL is still limited, and a consistent pattern has not been identified, most likely as a result of the phenotypic variety among patients and rarity of the disease. However, recent studies suggest higher levels of chromosomal imbalances (CI ≥ 5), as those observed with advance CTCL are associated with decreased survival (59). Of interest, abnormalities on the long arm of chromosome 15, in which pro-IL-16 is encoded (60), have been observed in patients with stage III and IV disease (59).…”
Section: Figurementioning
confidence: 99%
“…However, recent studies suggest higher levels of chromosomal imbalances (CI ≥ 5), as those observed with advance CTCL are associated with decreased survival (59). Of interest, abnormalities on the long arm of chromosome 15, in which pro-IL-16 is encoded (60), have been observed in patients with stage III and IV disease (59).…”
Section: Figurementioning
confidence: 99%